Hvad var dannelse? - Jepsen, Per (Studier i Pædagogisk Filosofi, 2018)
The article reconstructs the history of the concept of “Bildung” from its origin in the philosophy of Enlightenment to the crisis of education in the middle of the 20th century. After a presentation of the rise of the concept in the 18th and 19th century (Kant, Humboldt), the article discusses Horkheimer and Adornos critique of the classical tradition of Bildung and their diagnosis of the intellectual and educational climate in Th e Western World after the 2nd World War. Following this it presents the even more pessimistic view of the Austrian philosopher Konrad Paul Liessmann, who in his book Theorie der Unbildung from 2008 claims that the concept of “Bildung” today has no longer any normative impact on the theory and practice of education. In the final section I second this view by claiming that the tradition of Bildung is now closed: What is left of it is its history.